2018
DOI: 10.1111/ene.13689
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of gait variability in people with multiple sclerosis with fall history

Abstract: An association between low left hippocampal, putamen volumes and step time variability was found in PwMS with a history of falls, suggesting that brain structural characteristics may be related to falls and increased gait variability in PwMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Grey matter volumes of the putamen, caudate, globus pallidus and nucleus accumbens have been linked to the Timed 25‐ft Walk (T25FW) test in relapsing–remitting MS , whereas cerebellar volume has been associated with the T25FW test in primary progressive MS . Recently, an association between low left hippocampal, putamen volumes and step time variability was found in PwMS with a history of falls . In this context, the walk ratio may be advantageous as a marker of brain structure involved with locomotion, as it is an invariant feature of gait, allowing for an optimal balance between energy expenditure and forward propulsion for stability during walking .…”
Section: Introductionmentioning
confidence: 99%
“…Grey matter volumes of the putamen, caudate, globus pallidus and nucleus accumbens have been linked to the Timed 25‐ft Walk (T25FW) test in relapsing–remitting MS , whereas cerebellar volume has been associated with the T25FW test in primary progressive MS . Recently, an association between low left hippocampal, putamen volumes and step time variability was found in PwMS with a history of falls . In this context, the walk ratio may be advantageous as a marker of brain structure involved with locomotion, as it is an invariant feature of gait, allowing for an optimal balance between energy expenditure and forward propulsion for stability during walking .…”
Section: Introductionmentioning
confidence: 99%
“…The caudate nuclei have both behavioral and motor functions, including body and limb posture and controlling approach-attachment behaviors, respectively ( Kalron et al, 2020 ). Of note, the basal ganglia have strong anatomical and functional connections with the cortex, thalamus, and brainstem, and play a relevant role in initiating and controlling locomotion ( Villablanca, 2010 ; Onu et al, 2015 ; Kalron et al, 2018 , 2020 ). Previous studies examining the association between magnetic resonance imaging (MRI) measures and gait in PwMS have found that gray matter volume of the putamen, caudate, globus pallidus, and nucleus accumbens were all linked to the Timed 25-ft Walk (T25FW) test in relapsing-remitting MS ( Alexander et al, 1990 ; Onu et al, 2015 ), whereas cerebellar volume was associated with the T25FW test in primary progressive MS ( Alexander et al, 1990 ; Bhatia and Marsden, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining the association between magnetic resonance imaging (MRI) measures and gait in PwMS have found that gray matter volume of the putamen, caudate, globus pallidus, and nucleus accumbens were all linked to the Timed 25-ft Walk (T25FW) test in relapsing-remitting MS ( Alexander et al, 1990 ; Onu et al, 2015 ), whereas cerebellar volume was associated with the T25FW test in primary progressive MS ( Alexander et al, 1990 ; Bhatia and Marsden, 1994 ). Moreover, Kalron et al (2018) reported that PwMS with a history of falls exhibited reduced left caudate volume compared to non-fallers.…”
Section: Discussionmentioning
confidence: 99%
“…Gait variability has been shown to differentiate between both individuals with MS and healthy controls and MS fallers and non-fallers [44], as well as being linked to disability level, fatigue, and attention in persons with MS [45]. Therefore, the association between SMA DTI measures with gait variability (CVs) is particularly relevant, and represents a novel finding among persons with MS. A recent imaging study demonstrated relationships among increased gait variability and lower hippocampal and putamen volumes in MS fallers, but no DTI measures or tract-specific imaging was performed [46]. The relationship between higher gait variability and poorer SMA tract integrity and not with gait speed and spatiotemporal measures builds upon work by Hausdorff et al, who reported that gait variability (also referred to as unsteadiness or inconsistency and arrhythmicity of stepping) was closely associated with risk of falls in the elderly and in people with Parkinson's disease, whereas measures of gait speed and average gait cycle timing did not discriminate future fallers from non-fallers [47,48].…”
Section: Discussionmentioning
confidence: 99%